Embedded Engineering Education - Szewczyk, Roman; Kaštelan, Ivan; Temerinac, Miodrag; Barak, Moshe; Sruk, Vlado (Advances in Intelligent Systems and Computing, 2016)
This book focuses on the outcome of the European research project "FP7-ICT-2011-8 / 317882: Embedded Engineering Learning Platform" E2LP. Additionally, some experiences and researches outside this project have been included. This book provides information about the achieved results of the E2LP project as well as some broader views about the embedded engineering education. It captures project results and applications, methodologies, and evaluations. It leads to the history of computer architectures, brings a touch of the future in education tools and provides a valuable resource for anyone interested in embedded engineering education concepts, experiences and material. The book contents 12 original contributions and will open a broader discussion about the necessary knowledge and appropriate learning methods for the new profile of embedded engineers. As a result, the proposed Embedded Computer Engineering Learning Platform will help to educate a sufficient number of future engineers in Europe, capable of designing complex systems and maintaining a leadership in the area of embedded systems, thereby ensuring that our strongholds in automotive, avionics, industrial automation, mobile communications, telecoms and medical systems are able to develop. .